Halogen and chalcogen bonding host molecules for anion recognition and sensing - Lim, J (2017)
This thesis describes the preparation and study of acyclic, macrocyclic and mechanicallyinterlocked host molecules (MIMs) exploiting halogen and chalcogen bonding interactions for anion recognition and sensing. Chapter 1 introduces the field of anion supramolecular chemistry and interlocked structures, with emphasis on halogen and chalcogen bonding receptors, as well as their applications in catalysis, molecular recognition and nanotechnology. Chapter 2 explores the methodology development and synthesis of novel neutral and cationic macrocyclic and interlocked host molecules containing stable triazole-based halogen and chalcogen bonding motifs. The thermodynamic anion binding properties of these novel host molecules in wet and dry organic solvents are determined and compared. Chapter 3 details the applications and influences of halogen and chalcogen bonding interactions for electrochemical anion sensing. The ability of ferrocene-based halogen bonding receptors to enhance the sensitivity of redox anion sensing compared with hydrogen bonding host analogues is demonstrated. Chapter 4 investigates the unprecedented applications of halogen and chalcogen bonding interactions in enantioselective binding and sensing of chiral anions. The use of chiral [2]- and [3]rotaxanes for chiral anion discrimination is also demonstrated for the first time. Chapter 5 describes the exploitation of hydrophilic polyether-based cationic halogen bonding receptors for anion binding and sensing in water. In particular, the halogen bondingmediated recognition of oxoanions such as perrhenate and biologically-relevant phosphate species are discussed. Chapter 6 summarises the main conclusions of this thesis. Chapter 7 details the experimental procedures employed in this work, including synthetic protocols and characterisation data for novel compounds. Additional information pertaining to crystallographic data, electrochemical measurements and computational modelling procedures are provided in the Appendices.